Design of Adaptive 4D-8PSK-TCM Based on CNN for Low-Complexity - Kim, Song; Kim, Jae Hyun (Journal of Korean Institute of Communications and Information Sciences, 2021)
To provide services through satellite constellation requires more frequency resources and high-speed data transmission technology. The consultative committee for space data systems (CCSDS) recommends four dimensional 8-ary phase shift keying trellis coded modulation (4D-8PSK-TCM) for a high-speed transmission technology in the X-band, which is a frequency band for low Earth orbit satellite communication. The 4D-8PSK-TCM can reduce computational complexity with T-algorithm, however there is a problem with degraded bit error rate (BER) performance in high energy-to-noise specific density ratio (Eb/N0). In this paper, we explain the components of the 4D-8PSK-TCM system and design a CNN-based adaptive 4D-8PSK-TCM system that applies the parameters of T-Algorithm by estimation the Eb/N0 of signal to maintaining BER performance and minimize computational complexity for every Eb/N0.
Keywords: 4D-8PSK-TCM; CNN; satellite communications; T-algorithm